Relationship between depression and quality of life after myocardial infarction - Alen Džubur; Delila Lisica; Emir Hodžić; Edin Begić; Orhan Lepara; Almir Fajkić; Ena Gogić; Malik Ejubović (Medicinski glasnik, 2022)
Aim: To examine the prevalence of depression in patients after acute myocardial infarction (AMI), as well as the relationship between the depression and quality of life. Methods: The survey was conducted via sociodemographic questionnaire, Beck Depression Inventory (BDI), and Short Form 36 Health Survey questionnaire (SF-36). The result of SF-36 is expressed in subscales that make up the health status profile, i.e. physical functioning, physical role, emotional role, social functioning, mental health, vitality, pain and general health. Results: The study included 120 patients, of which 70 males and 50 females aged between 41 and 88 years (mean 64.73±11.218). All patients were hospitalized at the Clinical Centre of the University of Sarajevo, Clinic for Cardiovascular Disease and Rheumatism, due to complications caused by AMI. After AMI 59 (49.17%) patients had depression. Depression was negatively associated with physical functioning, physical role, emotional role, social functioning, mental health, vitality, pain and general health. Physical functioning (r= -0.701; p<0.01) and physical role (r = -0.538; p<0.01) had the highest correlation with depression. Conclusion: The evaluation of depressive symptoms after AMI is imperative, because the appearance of symptoms could have an effect on the patient's quality of life.
Keywords: cardiovascular diseases; mental health; patient care; public health